Lost causes: blended sentencing, second chances, and the Texas Youth Commission - Trulson, Chad R. (University of Texas Press, 2016)
Origins and discoveries -- The Determinate Sentencing Act in Texas -- The sheep that got lost -- Doing time in the Texas Youth Commission -- Another second chance -- The burden of second chances -- Three decades later -- The last word